2020
DOI: 10.15324/kjcls.2020.52.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Fecal Calprotectin Concentrations in Healthy Adults

Abstract: Fecal calprotectin (FC) is a marker used for the differential diagnosis of inflammatory bowel disease (IBD). FC is also used to determine the effects of treatment and recurrence prediction because of its non-decomposition by bacteria, relative week stability at room temperature, and its uniform distribution within feces. Healthy male and female adults between the age of 30 and 80 living in Jeju were selected for this study. The FC concentration in the healthy control group (N=45) was distributed widely as 0∼54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…Conversely, von Roon et al demonstrated that a cut-off of 100 µg/g may have higher diagnostic efficiency and precision than 50 µg/g [ 50 , 53 , 54 , 55 ]. Contrary to other studies, except that of Park et al [ 56 ], we did not observe any correlations between gender, BMI, and calprotectin concentration [ 54 , 56 , 57 , 58 , 59 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, von Roon et al demonstrated that a cut-off of 100 µg/g may have higher diagnostic efficiency and precision than 50 µg/g [ 50 , 53 , 54 , 55 ]. Contrary to other studies, except that of Park et al [ 56 ], we did not observe any correlations between gender, BMI, and calprotectin concentration [ 54 , 56 , 57 , 58 , 59 ].…”
Section: Discussioncontrasting
confidence: 99%
“…While there are few existing human studies on calprotectin, emerging evidence suggests that fecal calprotectin levels may vary across the life course and in age-related disease (5458) . For instance, in a population study of children aged 0 to 18 years old, median fecal calprotectin level among healthy infants under 1 year old was nearly twice that of children between 1 and 18 years old (5962) .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a population study of children aged 0 to 18 years old, median fecal calprotectin level among healthy infants under 1 year old was nearly twice that of children between 1 and 18 years old (5962) . One small study showed a 2-to 10-fold difference in fecal calprotectin among 45 healthy participants between 30 and 80 years old, however the vast majority of aging studies have examined calprotectin among cohorts with clinical disease diagnoses (46, 54, 57, 58, 63) . While our study was enriched for individuals with biologic and clinical AD, we determined that older participants had higher levels of fecal calprotectin while controlling for disease stage, and the results remained significant after performing sensitivity analyses that included only cognitively unimpaired participants, suggesting that advancing age increases gut inflammation independently of symptomatic AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations